(untitled) - Kumaravadivelu, B. (New Haven, 2003)
In this original book, B. Kumaravadivelu presents a macrostrategic framework designed to help both beginning and experienced teachers develop a systematic, coherent, and personal theory of practice. His book provides the tools a teacher needs in order to self-observe, self-analyze, and self-evaluate his or her own teaching acts.
Keywords: Language and languages,Language acquisition,Tiếng và ngôn ngữ; Study and teaching.,Dạy và học